2002
DOI: 10.1177/147323000203000312
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vitamins E and C on Fracture Healing in Rats

Abstract: Forty-eight rats were divided into four groups of 12. For 3 days, each group received the following vitamins in once-daily doses: group 1, vitamin E only; group 2, vitamin C only; group 3, vitamins E and C; and group 4, no treatment (control). The right tibia of each rat was fractured on day 4; the rats then received the same regimen three times a week (once-daily doses) until day 21. Fracture healing was evaluated radiologically by measuring the callus indices, and histologically by a 5-point grading scale. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
1
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 15 publications
0
64
1
6
Order By: Relevance
“…8 In a study in rats, however, no significant effect of α-tocopherol on tibial fracture healing was shown. 16 We believe that this apparent lack of an effect results from difficulties with the fixation of fractured rat tibiae and from the limited vascularization of the tibia, both of which have negative effects on fracture healing. For reasons of size we chose to use the rabbit femur, which enabled us to provide sufficient closed reduction and rigid fixation, important factors in fracture management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In a study in rats, however, no significant effect of α-tocopherol on tibial fracture healing was shown. 16 We believe that this apparent lack of an effect results from difficulties with the fixation of fractured rat tibiae and from the limited vascularization of the tibia, both of which have negative effects on fracture healing. For reasons of size we chose to use the rabbit femur, which enabled us to provide sufficient closed reduction and rigid fixation, important factors in fracture management.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C, one of the non-enzymatic aqueous antioxidants, has been shown to have a positive effect on fracture healing 16,17 and to increase α-tocopherol levels by reducing its metabolism. 18,19 A significant increase in fracture healing in rabbits receiving α-tocopherol was detected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have shown mixed results on the effectiveness of a-tocopherol supplementation in facilitating fracture healing in normal animal models. [24][25][26] Maniam et al 35 have measured directly lipid peroxidation and anti-oxidant enzyme activities in the bones of vitamin E-supplemented rats. They found that a-tocopherol supplementation did not have any effects on the lipid Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Studies have shown mixed results on the effects of a-tocopherol on fracture healing but all these studies were conducted in normal bone. Sarisozen et al 24 could not find any changes in the callous indices after 2 weeks of tibial fracture in normal rats supplemented with a-tocopherol compared to unsupplemented rats. Turk et al 25 concluded that a-tocopherol has positive effects on both the early and late phase of fracture healing.…”
mentioning
confidence: 99%
“…Nevertheless, previous studies have shown a positive effect of vitamin C in different healing processes. Yilmaz et al, in a study of experimental fractures in rats, suggested that vitamin C enhanced fracture-healing in comparison with that in a control group 14 , and Sarisozen et al confirmed that vitamin C accelerated fracture-healing in rats 15 . We did not study the time needed for fracture-healing.…”
Section: Discussionmentioning
confidence: 77%